A design of positioning book & information resources system - Abu Bakar, Hanis Maisarah; Khairuddin, Nur Zakiah; Razaki, Nur Liyana; Wan Mohd Noor, Wan Nadirah; Azman, Norhidayah (Universiti Teknologi MARA, Kedah, 2017)
A library is a place where all kinds of information resources are stored at. People who want to search and acquire information generally will go to library or other information institutions. Information is undeniably significant in human daily lives. This is because information can helps in decision-making process. As information is an essential thing, hence information should be easy to obtain and access. Therefore, people who are in the field of library and information area known as information professionals try very hard for better enhancement regarding information accessibility issues. Information will be useless if cannot access to it timely. Henceforth, this project design tends to focus on information accessibility issues. The project is aimed at improving ways for facilitating in locating and accessing any kinds of information resources. In short, we will design an innovation project of “Positioning Book & Information Resources System” that will ease library users in locating information resources. The idea of designing for this project was generated from group discussion. The design of this project is kinds of futuristic styles. We also will implement some technological aspects in designing of this project.